Improving Indigenous family engagement with the coronial system in New South Wales. (September 2021) - McCabe, Lindsay; George, Allen
This article explores the barriers experienced by Indigenous Australians that prevent adequate engagement with the coronial system in New South Wales. The findings presented here are the result of a qualitative study involving key legal professionals and advocates in the coronial jurisdiction. A number of significant shortcomings are identified, including inadequate funding, a lack of information and appropriate communication, and significant delays between time of death and conclusion of the inquest.